Involvement of cytotoxic Eomes-expressing CD4⁺ T cells in secondary progressive multiple sclerosis - Raveney, Ben J. E.; Sato, Wakiro; Takewaki, Daiki; Zhang, Chenyang; Kanazawa, Tomomi; Lin, Youwei; Okamoto, Tomoko; Araki, Manabu; Kimura, Yukio; Sato, Noriko; Sano, Terunori; Saito, Yuko; et al. (Proceedings of the National Academy of Sciences - PNAS, 2021)
Multiple sclerosis (MS), a putative autoimmune disease of the central nervous system (CNS), commonly presents as relapsing-remitting MS (RRMS), characterized by recurrent episodes of peripheral disabling symptoms resulting from inflammatory CNS damage. Many RRMS patients transition to a chronic disease course with progressive neurological dysfunctions (secondary progressive MS, SPMS), with the progression rate varying between patients and over time. SPMS pathogenesis is now linked to immune-cell–mediated processes, although the mechanisms driving SPMS transition and progression remain elusive, and SPMS lacks biomarkers and effective treatments. We report the crucial involvement of cytotoxic CD4⁺ T cells expressing Eomes (Eomes⁺ Th cells) in SPMS pathogenesis—a Th cell subset previously identified in a mouse model of late/chronic autoimmune CNS inflammation. Few Eomes⁺ Th cells circulate in RRMS patient peripheral blood (n = 44), primary progressive MS (PPMS) patients (n = 25), or healthy controls (n = 42), but Eomes⁺ Th cells were significantly increased in SPMS (n = 105, P < 0.0001). Strikingly, lymphocytes isolated from SPMS autopsy brain samples revealed CD4⁺ T cells infiltrating CNS that coexpressed Eomes and the cytotoxic molecule granzyme B. In particular, the Eomes⁺ Th cell levels were increased in SPMS patients in progressive disease phases versus SPMS patients without current disability increases (P < 0.0001). Moreover, Eomes level acted as a biomarker to predict SPMS patients at risk of diseaseworsening with over 80% accuracy (ROC-AUC = 0.8276). Overall, our results indicate that granzyme B-expressing Eomes⁺ T helper cells are involved in the pathogenesis of SPMS, with significant implications for SPMS biomarkers and therapeutic targets.